High Rate of Change of the Foot in Ecuadorian Children: The Need for Proper Shoe Design - Laura Martín-Casado; Inés Palomo-Fernández; Alberto Aldana-Caballero; Ivan Baltasar-Fernandez; Felix Marcos-Tejedor (MDPI AG, 2024)
Background: Physiological changes in the foot may be influenced by external factors such as shoe types or demographic parameters, leading to podiatric conditions in adulthood. The aim of this study was to assess the changes in morphological measurements of the feet of boys and girls during childhood and adolescence. Methods: A total of 1678 Ecuadorian children aged 8 to 17 years participated in the study. The length, width, and height of the foot were analyzed using a 3D scanner to obtain the arch height ratio for the diagnosis of pediatric flat foot. Results: Statistical differences were observed for lengths, widths, and perimeters of the foot in boys aged 5 to 15-16 years and girls aged 5 to 12-13 years. Differences in the height of the navicular bone were found in all age groups, with changes from 2.8 to 4.1% in boys and from 1.3 to 1.5% in girls. The greatest differences between boys and girls of the same age were found at 14 years old onwards. The highest prevalence of flat foot was found in 8-year-old girls (64.9%) and in 12-year-old boys (82.5%). Conclusions: The feet of Ecuadorian children develop progressively during childhood and adolescence. Boys presented with longer and wider feet than girls of the same age. The highest prevalence of flat foot was found in 12-year-old boys and 8-year-old girls.